Investigation of Pre-Service Teachers Views of Teaching as Profession - B. Akarsu; I. Afsin Kariper (University of Sofia, 2015)
The teaching profession has been transformed in the last century in terms of its approaches and structures, such as its instructional methods and learning settings. Such transformations affect the motivations that promote choosing it as a career. Recent studies conducted on the reasons for choosing the teaching profession have been carried out with pre- and in-service teachers' perspectives. The current study explores similar issues within broader views in terms of prospective teachers' personal views about two essential facets: "Prevailing views that teacher candidates hold about the profession"; "If any correlation exists between reasons for choosing teaching as a career and their disciplines". Participants were asked to identify their teaching philosophies and reasons for determining this career path in college. The data collection process took place between 2012 and 2014. A total of 253 pre-service teachers enrolled in teacher preparation programs agreed to participate in the study. The results of data analysis indicated that teacher candidates in different disciplines hold similar viewpoints on both research questions. In addition, they stated that they chose the teaching profession because 'It is a sacred job; the country needs better education; it is an ideal job for females'. Some correlation according to gender emerged for both of the research questions.